Evaluation of Geh gene expression in Staphylococcus aureus isolated from acne patients - Hussein, Mohammed (Tikrit Journal of Pure Science, 2024)
Acne vulgaris is a chronic skin disease that affects the hair follicle and sebaceous glands. Staphylococcus aureus colonizes human skin and causes infections ranging from local skin infections to systemic infections that may threaten human life due to its ability to produce many virulence factors and antibiotic resistance. The objective of this study is to measure the genetic expression of Geh gene responsible for producing the lipase enzyme from S. aureus isolated from acne patients. This study was conducted by collecting 130 swabs from acne patients at Tikrit Teaching Hospital. Using routine bacterial isolation and identification methods, 50 samples (38.4%) of the total samples were identified as S. aureus through its ability to grow in mannitol salt agar medium, the fermentation of mannitol sugar, and the change of the medium color to yellow. The Geh gene expression of ten S. aureus isolates from acne patients was examined using RT-PCR. The results showed that Geh gene was expressed in all isolates, with an expression ranging from 1.5 to 7.2, and that the mean folding of the Geh gene for ten samples was 4.2. This indicates the presence of high gene expression of the Geh gene in S. aureus isolates. Therefore, it is concluded that Lipase enzyme plays an important role in the pathogenesis of S. aureus in acne patients.